2015
DOI: 10.1111/deci.12172
|View full text |Cite
|
Sign up to set email alerts
|

Managing a Portfolio of Product Development Projects under Resource Constraints

Abstract: Managers of product development (PD) project portfolios face difficult decisions in allocating limited resources to minimize project or portfolio delay. Although PD projects are highly iterative (cyclical), almost all of the vast literature on project scheduling assumes that projects are acyclical. This article addresses this gap with a comprehensive analysis of 31 priority rules (PRs) on 18,480 portfolios containing 55,440 iterative projects. We find that the best PRs for iterative project portfolios differ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Studies have shown that the most suitable priority rules for iterative project portfolios differ significantly from those portfolios in which projects are acyclical [Browning and Yassine, 2015]. In this research, the performance of the 20 different priority rules used for acyclical projects are compared in the case of iterative-activity projects and 11 new rules were added that account for some characteristics of iterative projects.…”
Section: Priority Rule Basedmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that the most suitable priority rules for iterative project portfolios differ significantly from those portfolios in which projects are acyclical [Browning and Yassine, 2015]. In this research, the performance of the 20 different priority rules used for acyclical projects are compared in the case of iterative-activity projects and 11 new rules were added that account for some characteristics of iterative projects.…”
Section: Priority Rule Basedmentioning
confidence: 99%
“…In order to solve the RCMPSP, PRs remain a popular method mainly for their speed and simplicity [Vazquez et al, 2013] and because of the following reasons stated in [Browning and Yassine, 2015]:…”
Section: Base Modelmentioning
confidence: 99%
See 3 more Smart Citations